Study on some parameters affecting the degradation of methylene blue in water by electro-fenton using Ti/PbO2 anode - Le, Son Thanh; Dung , Tran Nguyen; Huong, Tran Thu; Dien, Nguyen Tran; Uyen, Dao Phuong (Vietnam Journal of Science and Technology, 2021)
In this work, the combination of two advanced oxidation processes, electro-Fenton (hydroxyl radical ●OH generated by reactions on cathode) and anodic oxidation (●OH produced directly on anode), in the same reactor was studied to evaluate the treatment of methylene blue (MB) dye in aqueous solutions. This electrochemical system was equipped with a commercial carbon felt cathode (9.5cm 12cm), lead dioxide-coated titanium anode (10 12cm), direct current (DC) and continuously aerated. The effects of operating parameters such as pH, applied current (I), catalyst concentration ([Fe2+]) and MB concentration (C0) on MB removal efficiency were investigated through monitoring MB concentration at different times by spectrophotometric method. An optimal process was achieved at the condition of [Fe2+] = 0.1 mM; pH 3.0; [Na2SO4] = 0.05 M; i = 2.5 mA.cm-2 and after 60 minutes of electrolysis, 92.19% of MB was removed which was far higher than the figure obtained by using individually electro-Fenton (73.77%) or anodic oxidation (58.04%). These experimental results have demonstrated that the combination of electro-Fenton and anodic oxidation using Ti/PbO2 electrode is a prospective method for destruction of persistent dyes